2018
DOI: 10.1002/2017sw001671
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Similarities Between WSA‐ENLIL+Cone Model and MAVEN in Situ Observations From November 2014 to March 2016

Abstract: Normal solar wind flows and intense solar transient events interact directly with the upper Martian atmosphere due to the absence of an intrinsic global planetary magnetic field. Since the launch of the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission, there are now new means to directly observe solar wind parameters at the planet's orbital location for limited time spans. Due to MAVEN's highly elliptical orbit, in situ measurements cannot be taken while MAVEN is inside Mars' magnetosheath. To model sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Lentz et al. (2018) also compared the model performance of WSA‐Enlil model in predicting the solar wind at Mars from late December 2015 to March 2016, and found that the model provide a MSE within the range of [1.07 × 10 4 , 1.59 × 10 4 ] km 2 /s 2 for solar wind speed, a MSE within the range of [8.00, 14.55] cm −6 for solar wind density, a MSE within the range of [7.80, 17.53] nT 2 for magnetic field. According to the RMSE of the HSA subgroup in predicting the solar wind at Mars listed in Table 3, our model provide MSE within the range of [0.94 × 10 4 , 1.03 × 10 4 ] km 2 /s 2 for solar wind speed, MSE within the range of [18.83, 22.28] cm −6 for solar wind density, MSE within the range of [14.74, 19.45] nT 2 for magnetic field.…”
Section: Comparing the Model's Performancementioning
confidence: 99%
“…Lentz et al. (2018) also compared the model performance of WSA‐Enlil model in predicting the solar wind at Mars from late December 2015 to March 2016, and found that the model provide a MSE within the range of [1.07 × 10 4 , 1.59 × 10 4 ] km 2 /s 2 for solar wind speed, a MSE within the range of [8.00, 14.55] cm −6 for solar wind density, a MSE within the range of [7.80, 17.53] nT 2 for magnetic field. According to the RMSE of the HSA subgroup in predicting the solar wind at Mars listed in Table 3, our model provide MSE within the range of [0.94 × 10 4 , 1.03 × 10 4 ] km 2 /s 2 for solar wind speed, MSE within the range of [18.83, 22.28] cm −6 for solar wind density, MSE within the range of [14.74, 19.45] nT 2 for magnetic field.…”
Section: Comparing the Model's Performancementioning
confidence: 99%
“…It maybe noted here that the WSA-ENLIL+Cone simulations are used only to get a general picture of what these events might have looked like on a larger scale at 1 and 1.5 AU. Though the WSA-ENLIL+Cone can provide short-term all-inclusive forecasts which are closer to the observations, the long-term forecasts may be imprecise in details (Lentz et al 2018;Falkenberg et al 2011). However, the predictions are reasonably accurate within 1 AU (Mays et al 2015); and therefore the simulations at STEREO locations (where observations are not available) are expected to be reasonable.…”
Section: A Wsa-enlil+cone Model Simulationsmentioning
confidence: 99%